High‐commitment HRM practices during the financial crisis in Portugal: Employees' and HR perspectives - Dello Russo, S. (2023)
Over the recent decades, organizations have had to face a number of major external shocks and crises. Acquiring a better understanding of how human resources are managed under such critical conditions constitutes the main purpose of this study. We conducted a study triangulating different sources (employees, HR managers, and secondary data) and types of data (quantitative and qualitative) to explore how employees in Portuguese organizations perceived the HR practices' implementation during the years of the financial crisis (2011–2014) and how HR managers explained it. Longitudinal evidence from 53 organizations attests to perceived decreasing trends, particularly in training and development and performance management. HR managers legitimize these trends, embracing conventions and revealing the impact of coercive and normative pressures. Our findings highlight the need for renewed attention to be paid to the contextual pressures on HR managers' decision-making and actions that could severely endanger their role as strategic partners and their embrace of sustainable HRM.